The Relationship Between Heavy Workload, Job Satisfaction, Employee Performance and Job Stress: An Application for Professional Accountants - Guney, Selami; Kaya, Abdulkadir (Int Journal Contemporary Economics & Administrative Sciences, 2024)
The high number of legal regulations, intense competition and rapid developments in business life create a heavy workload and serious stress on Certified Public Accountants. In this study, it is to determine the relationships between heavy workload, job satisfaction, poor performance and job stress experienced by Certified Public Accountants. According to the results of the at acceptable levels and that stress is significantly and favorably impacted by the perception of a heavy workload. On the other hand, stress was significantly and adversely impacted by perceptions of job satisfaction. Additionally, performance was significantly and favorably impacted by perceptions of a heavy workload and job satisfaction. On the other hand, work-related stress has had little impact on how well employees perform. In addition, it has been concluded that the stress loads of the professionals' increase depending on the workload and the stress increases with the new obligations that will occur in the workloads during the professional process.
Keywords: Certified Public Accountants; Workload; Job Satisfaction; Job Stress; Performance